THE IMPACT OF SYMMETRICAL VS. ASYMMETRICAL THERAPEUTIC EXERCISES ON POSTURAL ALIGNMENT AND TRUNK MUSCLE ENDURANCE IN CHILDREN WITH MILD SCOLIOSIS - Yezhova, Olha; Lohynova, Viktoria; Baryshok, Tetiana (Eastern Ukrainian Medical Journal, 2026)
Introduction. Scientific research has proven that therapeutic exercises provide an opportunity to achieve significant success in physical therapy for scoliosis in children. Both symmetrical and asymmetrical therapeutic exercises are used in rehabilitation interventions. In Ukraine, the rehabilitation package of the National Health Service of Ukraine (NHSU) provides physical therapy services for children with mild scoliosis (1-2 degree) for two weeks. However, the question of the impact of different types of therapeutic exercises in a two-week physical therapy programme remains open.Aim. This study aims to determine the effect of symmetrical and asymmetrical exercises on posture and strength of the abdominal muscles and back extensor strength in 10-12 year old children with mild scoliosis during a two-week physical therapy programme according to the NHS rehabilitation package.Materials and methods. The study included 25 patients aged 10-12 years, including 12 boys and 13 girls with diagnosed degenerative-dystrophic changes of the spine, namely S-shaped thoracolumbar scoliosis of the 2nd degree with different curvature angles (from 10 to 25° according to Cobb) or mild degree. All patients were divided into 2 groups, regardless of age and gender: a group of 11 people who participated in a physical therapy programme based on symmetrical therapeutic exercises, group training; a group of 14 people who participated in a physical therapy programme based on asymmetrical therapeutic exercises, individual training. At the beginning and at the end of the study, a survey was conducted, which included: New York Posture Rating Chart (NYPR) to assess posture in the frontal and sagittal planes, Adams test to assess posture in the horizontal plane, standardised functional tests to assess abdominal muscle strength and back extensor strength, height and weight measurements, and BMI calculation. An X-ray examination of the spine with the calculation of Cobb's angle and Risser's test score was performed only at the beginning of the study.The STATISTICA 6.0 software package was used for statistical processing of the study results. The probability level was taken as p < 0.05.Results. There is a decrease in postural asymmetry and an increase in functional endurance of the abdominal muscle strength and back extensor strength, regardless of gender and physical therapy programme, which confirms the success of different types and forms of therapeutic exercises to stabilise the muscular corset and reduce postural asymmetry. It should be noted that the SymG group showed more positive, but not significant, dynamics of functional indicators, but the only indicator, namely the NYPR posture score, was significantly improved in the AsymG.Conclusions. The use of an individual approach and asymmetrical exercises has a significantly better effect on postural symmetry, which indicates the feasibility of personalised development of physical therapy programmes for patients with more severe deformities of the posture and spine.